A quantitative, multi-national and multi-stakeholder assessment of barriers to the adoption of cell therapies. (9th August 2017) - Davies, Benjamin M; Smith, James; Rikabi, Sarah; Wartolowska, Karolina; Morrey, Mark; French, Anna; MacLaren, Robert; Williams, David; Bure, Kim; Pinedo-Villanueva, Rafael; Mathur, Anthony; Birchall, Martin; et al.
Cellular therapies, such as stem cell–based treatments, have been widely researched and numerous products and treatments have been developed. Despite this, there has been relatively limited use of these technologies in the healthcare sector. This study sought to investigate the perceived barriers to this more widespread adoption. An anonymous online questionnaire was developed, based on the findings of a pilot study. This was distributed to an audience of clinicians, researchers and commercial experts in 13 countries. The results were analysed for all respondents, and also sub-grouped by geographical region, and by profession of respondents. The results of the study showed that the most significant barrier was manufacturing, with other factors such as efficacy, regulation and cost-effectiveness being identified by the different groups. This study further demonstrates the need for these important issues to be addressed during the development of cellular therapies to enable more widespread adoption of these treatments.